Virtual Migration The Programming of Globalization - Aneesh, A. (Aneesh), 1964-; Project Muse. (Durham : Duke University Press, 2006)
Annotation Workers in India program software applications, transcribe medical dictation online, chase credit card debtors, and sell mobile phones, diet pills, and mortgages for companies based in other countries around the world. While their skills and labor migrate abroad, these workers remain Indian citizens, living and working in India. A. Aneesh calls this phenomenon virtual migration, and in this groundbreaking study he examines the emerging transnational virtual space where labor and vast quantities of code and data cross national boundaries, but the workers themselves do not. Through an analysis of the work of computer programmers in India working for the American software industry, Aneesh argues that the programming code connecting globally dispersed workers through data servers and computer screens is the key organizing structure behind the growing phenomenon of virtual migration. This rule of code, he contends, is a crucial and underexplored aspect of globalization. Aneesh draws on the sociology of science, social theory, and research on migration to illuminate the practical and theoretical ramifications of virtual migration. He combines these insights with his extensive ethnographic research in offices in three locations in Indiain Delhi, Gurgaon, and Noidaand one in New Jersey. Aneesh contrasts virtual migration with body shopping, the more familiar practice of physically bringing programmers from other countries to work on site, in this case, bringing them from India to New Jersey. A significant contribution to the social theory of globalization,Virtual Migrationmaps the expanding transnational space where globalization is enacted via computer programming code.
Of code and capital -- Programming globalization : visions and revisions -- Body shopping -- Virtual migration -- Action scripts : rule of the code -- Code as money -- Migrations : nations, capital, and the state.
Includes bibliographical references (p. [179]-190) and index.
Description based on print version record.
English.
JSTOR
Keywords: International economic integration; Information technology -- Economic aspects; Globalization -- Economic aspects; Contracting out; Labor supply -- Effect of technological innovations on; Labor mobility; Intégration économique internationale; Technologie de l'information -- Aspect économique.; Mondialisation; Impartition; Marché du travail -- Effets des innovations sur; Main-d'œuvre -- Mobilité.; globalism; POLITICAL SCIENCE / Labor & Industrial Relations; Contracting out; Globalization -- Economic aspects; Information technology -- Economic aspects; International economic integration; Labor mobility; Labor supply -- Effect of technological innovations on